Effect of core ceramic grinding on fracture behaviour of bilayered zirconia veneering ceramic systems under two loading schemes. Issue 12 (December 2016) - Jian, Yu-tao; Tang, Tian-yu; Swain, Michael V.; Wang, Xiao-dong; Zhao, Ke
Abstract: Objective: The aim of this in vitro study was to evaluate the effect of core ceramic grinding on the fracture behaviour of bilayered zirconia under two loading schemes. Methods: Interfacial surfaces of sandblasted zirconia disks (A) were ground with 80 (B), 120 (C) and 220 (D) grit diamond discs, respectively. Surface roughness and topographic analysis were performed using a confocal scanning laser microscope (CSLM) and a scanning electron microscopy (SEM). Relative monoclinic content was evaluated using X-ray diffraction analysis (XRD) then reevaluated after simulated veneer firing. Biaxial fracture strength ( σ ) and Weibull modulus ( m ) were calculated either with core in compression (subgroup Ac-Dc) or in tension (subgroup At-Dt). Facture surfaces were examined by SEM and energy dispersive X-ray spectroscopy (EDS). Maximum tensile stress at fracture was estimated by finite element analysis. Statistical data analysis was performed using Kruskal–Wallis and one-way ANOVA at a significance level of 0.05. Results: As grit size of the diamond disc increased, zirconia surface roughness decreased ( p  < 0.001). Thermal veneering treatment reversed the transformation of monoclinic phase observed after initial grinding. No difference in initial ( p  = 0.519 for subgroups Ac-Dc) and final fracture strength ( p  = 0.699 for subgroups Ac-Dc; p  = 0.328 for subgroups At-Dt) was found among the four groups for both loading schemes. While coarse grinding slightly increased final fracture strength reliability ( m ) for subgroups Ac-Dc. Two different modes of fracture were observed according to which material was on the bottom surface. Components of the liner porcelain remained on the zirconia surface after fracture for all groups. Significance: Technician grinding changed surface topography of zirconia ceramic material, but was not detrimental to the bilayered system strength after veneer application. Coarse grinding slightly improved the fracture strength reliability of the bilayered system tested with core in compression. It is recommended that veneering porcelain be applied directly after routine lab grinding of zirconia ceramic, and its application on rough zirconia cores may be preferred to enhance bond strength.